Do patients with well-functioning total hip arthroplasty achieve typical sagittal plane hip kinematics? A proof of concept study. Issue 2 (March 2023) - Langley, Ben; Page, Richard M; Whelton, Chris; Chalmers, Oliver; Morrison, Stewart C; Cramp, Mary; Dey, Paola; Board, Tim N
Background: Total hip arthroplasty (THA) patients have been shown to not achieve normal sagittal plane hip kinematics. However, previous studies have only conducted group level analysis and as such lack the sensitivity to highlight whether individual patients do achieve normal hip kinematics. As such this study looked to determine whether some patients with well-functioning THA achieve typical sagittal plane hip kinematics. Methods: Sagittal plane hip kinematics were collected on 11 well-functioning THA patients (Oxford Hip Score = 46 ± 3) and 10 asymptomatic controls using a 3-dimensional motion analysis system during self-paced walking. High-functioning THA patients were identified as those who displayed sagittal plane hip kinematics that were within the variance of the control group on average, and low-functioning patients as those who did not. Results: 5 THA patients were identified as high-functioning, displaying hip kinematics within the variance of the control group. High-functioning THA patients displayed peak hip flexion and extension values more closely aligned to asymptomatic control group than low-functioning patients. However, hip range of motion was comparable between high- and low-functioning total hip arthroplasty patients and reduced compared to controls. Conclusion: The presence of high-functioning THA patients who display comparable sagittal plane hip kinematics to controls suggests these patients do achieve normative function and challenges the conclusions of previous group level analysis. Understanding why some patients achieve better function post-operatively will aid pre- and post-operative practices to maximise functional recovery.